2007
DOI: 10.1002/gcc.20500
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes with abnormal expression changes in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is one of the most common and deadly forms of hematopoietic malignancies. We hypothesized that microarray studies could identify previously unrecognized expression changes that occur only in AML blasts. We were particularly interested in those genes with increased expression in AML, believing that these genes may be potential therapeutic targets. To test this hypothesis, we compared gene expression profiles between normal hematopoietic cells from 38 healthy donors and leukemic blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
158
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 90 publications
2
158
1
Order By: Relevance
“…muscle and nervous systems) (Ishiguro et al, 2004;Shiraishi et al, 2004;Bortoloso et al, 2006). Current studies showed that Homer3 were abnormal expressed in blasts in AML (Stirewalt et al, 2008) and myelodysplastic syndrome (MDS) (data not shown). And decreased expression for Homer3 was associated with a poor outcome in AML (Valk et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…muscle and nervous systems) (Ishiguro et al, 2004;Shiraishi et al, 2004;Bortoloso et al, 2006). Current studies showed that Homer3 were abnormal expressed in blasts in AML (Stirewalt et al, 2008) and myelodysplastic syndrome (MDS) (data not shown). And decreased expression for Homer3 was associated with a poor outcome in AML (Valk et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, momentary events (cell processing, target isolation and enzyme efficiencies) directly impact the cells and the data. 3,10 Consequentially, quality controls are essential for proper analyses and interpretation of the results. In addition, most of these platforms have a finite number of potential targets that can be examined, potentially missing critical genetic, epigenetic, and/or expression changes.…”
Section: Table 1 To Be Inserted Here Methods To Examine the Regulatormentioning
confidence: 99%
“…However, these findings must be interpreted with caution and in full view of critical differences between normal and diseased cellular biology. [1][2][3] Several fundamental issues (outlined below) must be addressed to effectively design experiments and to appropriately interpret results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations